2022
DOI: 10.1186/s12935-022-02481-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tRNA-derived small RNAs signature as a predictive and prognostic biomarker in lung adenocarcinoma

Abstract: Background The prevalence of lung adenocarcinoma (LUAD) has increased, thus novel biomarkers for its early diagnosis is becoming more important than ever. tRNA-derived small RNA (tsRNA) is a new class of non-coding RNA which has important regulatory roles in cancer biology. This study was designed to identify novel predictive and prognostic tsRNA biomarkers. Methods tsRNAs were identified and performed differential expression analysis from 10 plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Nowadays, machine learning has been increasingly applied for combined analysis of multiple molecules to achieve higher prediction accuracy. Wang et al established a model by support vector machine, combining three hub tRFs (tRF-16-L85J3KE, tRF-21-RK9P4P9L0 and tRF-16-PSQP4PE) to predict lung adenocarcinoma with an AUC 0.99 in plasma and 0.92 in tissues [ 140 ]. By contrast, the performance of these single tRF to distinguish lung adenocarcinoma in both plasma and tissue was very poor [ 140 ].…”
Section: Biological Roles and Clinical Values Of Trfs In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, machine learning has been increasingly applied for combined analysis of multiple molecules to achieve higher prediction accuracy. Wang et al established a model by support vector machine, combining three hub tRFs (tRF-16-L85J3KE, tRF-21-RK9P4P9L0 and tRF-16-PSQP4PE) to predict lung adenocarcinoma with an AUC 0.99 in plasma and 0.92 in tissues [ 140 ]. By contrast, the performance of these single tRF to distinguish lung adenocarcinoma in both plasma and tissue was very poor [ 140 ].…”
Section: Biological Roles and Clinical Values Of Trfs In Cancermentioning
confidence: 99%
“…Wang et al established a model by support vector machine, combining three hub tRFs (tRF-16-L85J3KE, tRF-21-RK9P4P9L0 and tRF-16-PSQP4PE) to predict lung adenocarcinoma with an AUC 0.99 in plasma and 0.92 in tissues [ 140 ]. By contrast, the performance of these single tRF to distinguish lung adenocarcinoma in both plasma and tissue was very poor [ 140 ]. Another recent study also demonstrated that machine learning diagnostic models constructed with serum RNAs including tRFs, microRNAs, miscellaneous RNAs, and isomiRs could predict lung cancer up to 10 years prior to diagnosis, with a top AUC up to 0.9 [ 186 ].…”
Section: Biological Roles and Clinical Values Of Trfs In Cancermentioning
confidence: 99%
“…Some tsRNAs can be prognostic biomarkers because of their elevated expression in patients ( Tang et al, 2021 ). Such overexpressed tsRNAs can be knocked down by specific siRNAs which are regarded as therapeutic targets ( Wang et al, 2022b ). Some other tsRNAs are downregulated in patients, so the restoration of their intracellular levels may inhibit the disease progression ( Xiao et al, 2022 ).…”
Section: Roles Of Trna-derived Small Rnas In Different Diseasesmentioning
confidence: 99%
“…The Area Under Curve (AUC) of these three tsRNAs reached 0.92 when they were combined to diagnose LUAD, suggesting good diagnostic efficacy. Additionally, tRF-21-RK9P4P9L0 was negatively correlated with LUAD prognosis, and inhibition of tRF-21-RK9P4P9L0 expression diminished the proliferation, migration, and invasive ability of LC cell lines [ 97 ]. In the plasma of CRC patients, the expression level of 5-tRF-GlyGCC was significantly elevated with an AUC of 0.882 and was further increased to 0.926 after combined with carcinoembryonic antigen and Carbohydrate antigen199, suggesting its good diagnostic efficacy for CRC [ 98 ].…”
Section: Clinical Application Value Of Tsrnas In Cancer: As Biomarker...mentioning
confidence: 99%